Out in the Open: Investigating Passive Airborne eDNA Detection of Bats at Artificial Feeding Stations - Daniel E. Sanchez; Faith M. Walker; Savannah J. Marriott; Anna L. Riley; Sarah Stankavich; Amanda M. Adams; Donald Solick; Doug Bradley; Christian Newman (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) is a valuable biomonitoring tool, but application in terrestrial settings remains challenging due to a lack of generalizable sampling approaches. With bat species needing urgent research attention, airborne eDNA may offer this generalizability, as current eDNA sampling for bats is mostly limited to conspicuous sources (e.g., guano). While previous studies detected bats from roosts and open‐air sites using active air sampling, it remains uncertain whether bats can be readily detected from the open air using passive approaches. In central Texas, we used passive air sampling to determine if we could recover bat assemblages with metabarcoding and an imperiled focal species (tricolored bat, Perimyotis subflavus) with qPCR. Outside two cave locations, we positioned passive air samplers (two collection media per sampler; n = 24 media) near artificial prey patches, monitoring acoustically for bat activity and foraging. In the lab, we subjected the media to multiple eDNA extraction methods, direct DNA extraction, and two resuspension‐concentration approaches (filtration and pelleting). Metabarcoding allowed the detection of two bat species within a single sample, while qPCR allowed detection of P. subflavus in two samples. Although the detections all came from direct extraction, pelleting substantially improved taxonomic recovery and sample success for vertebrates overall. Detection of bat eDNA from passive samplers establishes a lower bound possibility for open‐air settings, and the low number of detections highlights the need for improved sampling strategies. We offer recommendations to enhance future efforts and introduce a qPCR assay for P. subflavus that can be used in a variety of eDNA contexts.